Assessing the roles of L1 and meaning knowledge in processing and production of English collocations among Chinese EFL learners - Wu, Yong Ping; Hasliza Abd Halim,; Mohd Hilmi Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present study examined the roles of first language (L1) and meaning knowledge of nodes in the processing and written production of English collocations among Chinese EFL learners. Twenty-four congruent collocations (can be expressed by a literal L1 translation equivalent) and 24 incongruent collocations (cannot be translated into L1 word by word) were examined by a timed phrase acceptability judgment task and a productive test. Based on the method of the Word Associates Test (Read, 1993), a meaning recognition test was developed to examine learners’ knowledge of multiple meanings of nodes. Results of pair-sample t-tests revealed that learners had better performance on congruent collocations than on incongruent collocations in both processing and written production, with shorter response times, fewer error rates in processing and higher production scores. A two-tailed Pearson correlation analysis indicated that learners’ meaning knowledge of node words had a moderate positive correlation with congruent collocation processing, incongruent collocation processing, congruent collocation production and incongruent collocation production, respectively, and the correlations with incongruent collocations were stronger than that with congruent collocations, especially in processing. The results implied that L1 and learners’ meaning knowledge of nodes played positive roles in both the processing and written production of L2 collocations. Some direct implications for L2 collocation teaching practice were discussed.